Quality evaluation of “safeer” portal for Saudi students studying abroad - Taha, Imad; Alzuabi, Haifa (2012)
The purpose of this research was to evaluate the quality of Safeer portal. “Safeer” is a portal through which a student can apply for any of the 86 available academic, administrative and financial services. It was launched on Sunday 29th of January 2009; to link the Saudi ministry of higher education to Saudi cultural missions around the world. The quality was evaluated by seven experts and eight factors. Every dimension was evaluated by different number of items on 5 Likert scales. The evaluation instrument was the survey developed by the researchers upon the reviewed literature. It was found that, the Safeer portal quality is fairly good by 75% and it needs further improvement and development by 25%. The researchers recommend further investigation on empirical surveys, in order to develop more acceptable and authentic instrument. Also, it needs further understanding of evaluators. The evaluators’ uncertainty is an ambiguity issue raised in the difference between internal consistency of the survey and the lack of their concordance.